PENGARUH PEMASARAN RELASIONAL TERHADAP LOYALITAS PELANGGAN PADA PT. MELIA SEHAT SEJAHTERA STOKIS MEDAN - Rumiaty Manurung; Endang Sulistya Rini (Jurnal Media Informasi Manajemen, 2013)
ABSTRACT The purpose of this research is to investigate and analyze the effect of relationship marketing on customer loyalty in PT Melia Sehat Sejahtera Stokis Medan. This research is associative. Methods of collect the data is the primary data using questionnaires and secondary data to study documentation. This research population is 259 distributors, with a sample size of 72 distributors with Simple Random Sampling. Data analysis method used is descriptive quantitatively using simple linear regression. The results showed that the relationship marketing has a positive and significant effect on customer loyalty in PT. Melia Sehat Sejahtera Stokis Medan. Keywords: Relationship Marketing and Customer Loyalty